TDO2 + cancer-associated fibroblasts mediate cutaneous squamous cell carcinoma immune escape via impeding infiltration of CD8 + T cells - Fangqi Lu; Guorong Yan; Zijun Zhao; Zhe Zheng; Yuhao Wu; Long Wen; Yeqaing Liu; Qingyu Zeng; Guolong Zhang (Cancer Immunology, Immunotherapy)
Abstract Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer, originating from the malignant proliferation of squamous epithelial cells. However, its pathogenesis remains unclear. To further explore the mechanisms underlying cSCC, we analyzed the data from one single-cell RNA sequencing study and discovered a significant upregulation of tryptophan 2,3-dioxygenase (TDO2) in the cancer-associated fibroblasts (CAFs). Nonetheless, the specific expression and potential biological significance of TDO2 in cSCC have not yet been reported. In this study, we confirmed that TDO2 is highly expressed in CAFs of cSCC. Clinical correlation analysis indicated that high TDO2 expression was significantly associated with poor tumor differentiation. Furthermore, increased TDO2 expression in cSCC correlated with reduced CD8 + T cell infiltration, suggesting its role in modulating immune responses. TDO2 inhibitors significantly reduced the size and number of tumors in mice and effectively increased CD8 + T cell infiltration. RNA sequencing analysis revealed that TDO2 inhibitors modulate immune cell activity and downregulate the PI3K-Akt signaling pathway. In summary, our study demonstrates that TDO2 + CAFs induce immune evasion by inhibiting CD8 + T cell infiltration in cSCC. Inhibiting TDO2 could enhance antitumor immune responses, providing a promising strategy to improve treatment outcomes in cSCC.